2012
DOI: 10.2169/internalmedicine.51.7326
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Computed Tomography Findings in 39 Cases of <i>Streptococcus pneumoniae</i> Pneumonia

Abstract: Objective The main objective of our study was to describe the pulmonary distribution of consolidation and ground-glass opacity (GGO) in chest computed tomography (CT) scans of Streptococcus pneumoniae pneumonia. In addition, the percentage of other pulmonary abnormalities was also reported. Methods We retrospectively evaluated chest CT examinations performed between November 2008 and January 2010 in 39 patients with S. pneumoniae pneumonia. Eight patients with Haemophilus influenzae pneumonia were also include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…However, the authors did not attempt to evaluate improved clinical outcomes or management changes. Other investigators have tried to demonstrate unique or specific findings on CT scans compared to plain radiography for particular pathogens …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors did not attempt to evaluate improved clinical outcomes or management changes. Other investigators have tried to demonstrate unique or specific findings on CT scans compared to plain radiography for particular pathogens …”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have tried to demonstrate unique or specific findings on CT scans compared to plain radiography for particular pathogens. [11][12][13] We attempted to identify specific features of patients presenting with pneumonia that could assist clinicians in the decision-making process as it relates to ordering a CT scan. CT scans were performed more frequently on subjects who were younger, had lower severity of illness, and were admitted from the community.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of microbial agents, including typical and atypical pathogens, can cause CAP. A considerable number of studies on the CT findings of CAP triggered by different pathogens, including Streptococcus pneumoniae, [6][7][8] Klebsiella pneumoniae, 9,10 Mycoplasma pneumoniae, [11][12][13][14] Chlamydia pneumoniae 14,15 and Legionella pneumophila, 16,17 have been published. Patients with CAP attributed to a specific pathogen present with more than 1 CT pattern, although 1 of these patterns predominates.…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic bacteria reached the alveoli and multiplied, leading to inflammatory exudate. The secretions of the bacteria were mainly along the small alveolar foramina and a small airway spread to the center, thus forming a subpleural nonsegmental lobar consolidation [ 7 ]. Pneumococcal pneumonia is a very common CAP, and pathology is a fibrinous inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumococcal pneumonia is a very common CAP, and pathology is a fibrinous inflammation. Results of the CT scan showed that lobar consolidation at first occurred in the visceral pleura of the lung periphery, usually close to the interlobular fissure, and gradually extended to the lung segment boundaries and spread to the center, eventually involving the entire lobe [ 7 , 8 ]. Bronchi were usually kept open, causing bronchogram in the consolidated area.…”
Section: Discussionmentioning
confidence: 99%